Managers' Risk Preferences and Firm Training Investments - Marco Caliendo; Deborah A. Cobb-Clark; Harald Pfeifer; Arne Uhlendorff; Caroline Wehner (Institute of Labor Economics (IZA), 2022)
We provide the first estimates of the impact of managers' risk preferences on their training allocation decisions. Our conceptual framework links managers' risk preferences to firms' training decisions through the bonuses they expect to receive. Risk-averse managers are expected to select workers with low turnover risk and invest in specific rather than general training. Empirical evidence supporting these predictions is provided using a novel vignette study embedded in a nationally representative survey of firm managers. Risk-tolerant and risk-averse decision makers have significantly different training preferences. Risk aversion results in increased sensitivity to turnover risk. Managers who are risk-averse offer significantly less general training and, in some cases, are more reluctant to train workers with a history of job mobility. All managers, irrespective of their risk preferences, are sensitive to the investment risk associated with training, avoiding training that is more costly or targets those with less occupational expertise or nearing retirement. This suggests the risks of training are primarily due to the risk that trained workers will leave the firm (turnover risk) rather than the risk that the benefits of training do not outweigh the costs (investment risk).
Keywords: J24; D22; D91; 330; manager decisions; employee training; risk attitudes; human capital investments